Construction of novel hypoxia-related gene model for prognosis and tumor microenvironment in endometrial carcinoma - Chen, Junfeng; Wang, Guocheng; Zhang, Donghai; Luo, Xiaomei; Zhang, Da; Zhang, Yongli (Frontiers in Endocrinology, 2022)
Introduction Endometrial cancer is currently one of the three most common female reproductive cancers, which seriously threatens women’s lives and health. Hypoxia disrupts the tumor microenvironment, thereby affecting tumor progression and drug resistance. Methods We established hypoxia-related gene model to predict patient prognosis and 1-, 3-, and 5-year overall survival rates. Then, the expression level of hypoxia-related genes and survival data were extracted for comprehensive analysis by Cox regression analysis, and the model was established. Results We analyzed the survival and prognosis of patients in the high and low-risk groups. The Kaplan-Meier curve showed that the low-risk group is associated with a better survival rate. The 1-, 3-, and 5-year AUC values of the model were 0.680, 0.698, and 0.687, respectively. Finally, we found that LAG3 may be a potential immune checkpoint for endometrial cancer. Conclusion We found four hypoxia-related genes (ANXA2, AKAP12, NR3C1, and GPI) associated with prognosis. The hypoxia-related gene model can also predict prognosis and tumor microenvironment in endometrial cancer.